Mechanism of Commuting the Death Penalty to Imprisonment Based on Scientific Evidence - Mahar, Yovianes (Institute Of computer Science (IOCS), 2025)
This study discusses the application of the death penalty in the National Criminal Code (KUHP Nasional)) and the legal mechanism related to the commuting of the death penalty to imprisonment for 20 years or life. Although the National Criminal Code accommodates the death penalty as an alternative punishment, there is an urgency to reconstruct a clear mechanism related to the commuting of criminal forms, in order to avoid abuse of power. This study uses legal research methods, with psychological, and philosophical approaches, to analyze the differences between the provisions of the death penalty in the colonial and national codes, as well as the implications of their application. One of the main focuses is the importance of psychological assessment in determining whether a convict deserves a reduced sentence, taking into account factors such as remorse, empathy, and emotional stability. The results of this study show that the punishment commuting mechanism requires further regulation and transparent evaluation to ensure fair and accountable decisions